2005
DOI: 10.1182/blood-2004-04-1569
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular phosphorylation converts pigment epithelium–derived factor from a neurotrophic to an antiangiogenic factor

Abstract: The pigment epithelium-derived factor (PEDF) belongs to the superfamily of serine protease inhibitors (serpin). There have been 2 distinct functions attributed to this factor, which can act either as a neurotrophic or as an antiangiogenic factor. Besides its localization in the eye, PEDF was recently reported to be present also in human plasma. We found that PEDF purified from plasma is a phosphoprotein, which is extracellularly phosphorylated by protein kinase CK2 (CK2) and to a lesser degree, intracellularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 30 publications
2
71
0
Order By: Relevance
“…(Maik-Rachline et al (2004)). Lysates were subsequently immunoprecipitated with rabbit anti-occludin antibody.…”
Section: Alakaline-phosphatase Pre-treatmentmentioning
confidence: 99%
“…(Maik-Rachline et al (2004)). Lysates were subsequently immunoprecipitated with rabbit anti-occludin antibody.…”
Section: Alakaline-phosphatase Pre-treatmentmentioning
confidence: 99%
“…It was also shown that PDGF, the other growth factor implicated in angiogenesis, is phosphorylated by CK2. The CK2 phosphorylated form of PDGF has an elevated anti-angiogenic activity [48,49]. Recently, it turned out that PDG induced the CK2a' subunit expression [50].…”
Section: Ck2 and Angiogenesismentioning
confidence: 99%
“…PEDF is one of the most promising anti-angiogenic factors; a number of studies have demonstrated its anti-angiogenic effects in various tumor models, including retinoblastoma, neuroblastoma, prostate cancer, melanoma, Wilms' tumor, pancreatic adenocarcinoma, hepatoblastoma, osteosarcoma, chondrosarcoma, human cervical carcinoma, gastric carcinoma, nasopharyngeal carcinoma, Lewis lung carcinoma, colorectal peritoneal carcinoma, glioma and breast cancer xenografts (20)(21)(22)(23)(24). The anti-angiogenic effect of PEDF is performed primarily through the disruption of microvascular network distribution (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%